Factors Associated with Early Child Development: A Pre-Screening Study - Setiawan, Erwin; Handoko, Willy; Andriani, Rini (JURNAL INFO KESEHATAN, 2023)
Early child development is a critical phase for lifelong health, resulting from the influence of various factors. The present study assessed the factors associated with children’s deviant development. This cross-sectional study was conducted on 88 infants aged 6-12 months in six Public Health Centres in East Pontianak, West Kalimantan. Breastfeeding duration at each session, the frequency in a day and the length of breastfeeding in months, mothers’ knowledge, behavior, and the habit of squeezing in children were the risk factors for early development. A chi-square analysis of the relationship between risk factors and children’s development. Overall, the results indicated that shorter breastfeeding duration at each session (p=0.027), non-exclusive breastfeeding (p=0.050), and low mothers’ knowledge (p=0.032) significantly affected children’s development. These results suggested that exclusive breastfeeding and enough knowledge enhance infant development.